Green School Oriented Guided Inquiry-Based Science E-Book: Effectiveness Analysis on Increasing Environmental Literacy - Nurul Zakiatin Nafsih; Usmeldi Usmeldi (Postgraduate, University of Mataram, 2022)
The world has entered the era of Industry Revolution 4.0, which is characterized by the advancing development of science. The ease of accessing information is increasing along with the development of science. Education can be a solution to the problems of life. Education can change a person's behavior in a more positive direction. Learning in the 4.0 era utilizes technology to facilitate the learning process. The advantage of using technology is that it makes it easier to access information without boundaries of space and time. The use of technology can be applied to compiling and developing teaching materials in the form of electronic books. Improving the quality of learning is prioritized in core activities so that appropriate learning models are needed to support learning activities. The learning model that can be used is the guided inquiry learning model. Guided inquiry can be used as learning models. This study was aimed to find out the effectiveness of Green School Oriented Guided Inquiry-Based Science E-Book. This research was used Plomp development model. The product in the form of a guided inquiry-based science e-book was tested on 31 class VIII students of Junior high school 17 Padang. Based on the results of the research and the explanation of the discussion, we can conclude that guided research-based e-books with green school orientation are effective in improving the environmental literacy of junior high school students. This is reflected in the value of knowledge, and learners' attitudes towards the environment are increasing.